Comments on “Rapid Image Reconstruction of Structured Illumination Microscopy Directly in the Spatial Domain” - Michael Somekh (IEEE Photonics Journal, 2021)
This comment shows that the formulation used in the above paper has been presented in virtually the same form in a previous paper. The comment also emphasizes that spatial domain reconstruction for structured light microscopy is a useful supplement to Fourier based algorithms.